Literatur Review : Hubungan Tingkat Pengetahuan dan Sikap Remaja terhadap Perilaku Pencegahan HIV/AIDS - Fathiyyatussabillah; Kumalasary, Diyanah; Yulianti, Ria (Sinar : Jurnal Kebidanan, 2026)
Background:  HIV/AIDS remains a major global public health issue, including in Indonesia, where the number of cases continues to rise annually. In 2024, the Ministry of Health recorded 35,415 new HIV cases and 12,481 new AIDS cases. Adolescents represent a vulnerable group for HIV transmission due to limited knowledge and understanding of reproductive health and preventive behaviors. Purpose: This study aims to determine the relationship between adolescents’ knowledge and attitudes toward HIV/AIDS prevention behaviors. Methods: This study employed a literature review method by analyzing thirty national journals published between 2019 and 2024, obtained through the Google Scholar database. Results: The review of thirty journals revealed a significant relationship between adolescents’ knowledge and attitudes and their HIV/AIDS prevention behaviors. Adolescents with limited knowledge of HIV/AIDS tend to engage in inappropriate behaviors, making prevention more difficult, whereas those with good knowledge demonstrate higher self-confidence and positive attitudes toward preventive actions. Conclusion: The findings indicate a strong correlation between adolescents’ knowledge and attitudes and their preventive behaviors toward HIV/AIDS. Enhancing knowledge effectively fosters positive attitudes and preventive behaviors among adolescents. Therefore, continuous efforts are needed through youth education, strengthened health promotion by healthcare workers, integration of reproductive health education in schools, and active parental involvement in providing accurate understanding. Further research is recommended to explore other factors influencing HIV/AIDS prevention behaviors, such as the role of media, social environment, and family support.